Effects of Dietary Energy and Methionine Sources on Productive Performance and Carcass Yield in Broiler Chickens - Choawit Rakangtong; Chaiyapoom Bunchasak (Agriculture and Natural Resources, 2010)
An experiment was conducted to determine the effects of two dietary energy sources (corn and cassava) and three types of dietary methionine (Met) supplementation (without methionine supplementation, liquid DL-methionine hydroxy analog-free acid (LMA) supplementation and dry DLmethionine (DLM) supplementation) on the growth performance and carcass yield of broiler chicks during 0-6 weeks of age. The experiment was a completely randomized design in a 2 × 3 fractional factorial. Nine hundred commercial male broiler chicks (Ross strain) were divided into six groups, and each group consisted of six replicates of 25 chicks each. The chicks were kept in floor pens, and water and feed were supplied ad libitum throughout the experimental period. The six experimental diets were: 1) corn-soybean diet deficient in methionine, 2) corn-soybean diet supplemented with DLM, 3) cornsoybean diet supplemented with LMA, 4) cassava-soybean diet deficient in methionine, 5) cassavasoybean diet supplemented with DLM and 6) cassava-soybean diet supplemented with LMA. The experiment assumed that 100 units of liquid LMA could be replaced by 88 units of DLM. Weight gains, feed conversion ratio (FCR) and average daily gain (ADG) in chicks fed the diets supplemented with LMA or DLM were significantly greater than those in chicks fed the methionine-deficient diets (P<0.05). The weights of the eviscerated carcass, pectoralis major, pectoralis minor and wings were increased by DLM and LMA supplementation (P<0.05). Dietary energy sources analysis indicated that the meat yield of chicks fed the cassava-soybean diet was lower than for chicks fed the corn-soybean diet, while the abdominal fat level was higher. The results indicated that chicks fed the cassava-soybean base diet showed lower productive performance than chicks fed the corn-soybean base diet. The effect of methionine source (DLM and LMA) on the growth performance and carcass yield of chicks was not significantly different. In conclusion, adding methionine could prevent the negative impact of amino acid imbalance and improve the energy utilization of chicks fed on a diet based on cassava-soybean.